Preliminary Estimation of Marine Recreational Fisheries (MRF) in the Time of COVID-19 Pandemic: The Marche Region Case Study (Adriatic Sea, Italy) - Bolognini, Luca; Cevenini, Fabio; Franza, Valentina; Guicciardi, Stefano; Petetta, Andrea; Santangelo, Laura; Scanu, Martina; Grati, Fabio (Frontiers in Marine Science, 2022)
Marine Recreational Fishing (MRF) is a highly attended complex activity, extremely evident along the coastlines, and mainly practiced among riparian communities. For that reason, this activity plays an important role to effectively contribute to the collective well-being, both from the social and economic points of view. However, it may negatively affect the fish stocks and the marine environment in general, mainly due to the removal of biological resources. The growing need to evaluate the magnitude of marine recreational fishing is recognized worldwide, especially in the last decade, when inclusive fishing programs began to focus their attention on this fishing activity. Based on its unexpected evidence and its wider repercussion on social behavior, the COVID-19 pandemic is considered by the scientific community as one of the most unique opportunities to better understand the social phenomenon and their repercussion on the environment. In this work will be reported very preliminary results on the consistency of marine recreational fishing in the case study of the Marche region (Italy). Number of recreational fishers and fishing effort were estimated through a telephone survey conducted in the Italian side of the Northern Adriatic Sea (FAO GFCM Geographical Sub Area 17) by interviewing 580 households. The sampling strategy also included a recall survey, which was carried out every month on a list of recruited fishers. In this manner, additional information was collected, such as detailed fishing effort, catches, and expenditures. In addition, biological data of catches were estimated through several on-site surveys. The information collected from January and December 2020 was affected by the COVID-19 pandemic in terms of social restrictions and access to marine places, inevitably impacting on marine recreational fishing features, including the biological resources and the related economic aspects.